The Development Of Holistic Personality: An Integrative Approach - Embong, Rahimah; Shafik, Siti Saadiah; Wan Yusof, W.M. (2013)
This paper aims to discuss about the development of holistic personality from integrated approach which is imperative in facing the new millennium and its challenges. The first part will discuss on the issue of disintegrated personality which creates dilemma facing the humankind in this new millennium. The second part will examine the characteristic and indicators of holistic personality from an integrated approach. The third part will suggest some recommendations and implications on how to develop the holistic personality. The study elucidates the world today witnesses numerous problems such as corruption, oppression, depression, and aggression. These phenomena are infecting even those highly educated people throughout world including Eastern and Western countries. It resulted from the disintegrated personality, rich in knowledge and properties but poor in ethics. The existing system of education faced failure in the East as well as in the West. For instance in the United States of America as mentioned by Matthew Lipman (1991,28-29) in his book Thinking in Education, during 1980’s, the American Secretary of Education, William Bennet and his assistant, Chester Finn and other such authorities complained that Americans were poorly served by the educational system because the products of this system knew little, or nothing worth knowing. Consequently, the entire system of education was in crisis. The knowledge taught was not relevant to students’ life, but applicable only to examination as a permit for entering into life. Therefore, there is an urgent need to develop an individual with a holistic personality. He or she should be a good man, a competent leader, a wise professional and a seeker of the Truth. He or she should possess good moral characters which is the manifestation of high spirituality; and has intellectual knowledge and professional acumen to enable him to be globally competent and socially and environmentally conscious. The noble aim to produce such personality may be realized through Holistic Integrated Curriculum (HIC). HIC provides comprehensive personality development spiritually, morally, intellectually, professionally, socially and physically. Thus, to develop holistic personality, seven main areas should be considered. These are spiritual liberation, moral development, cultivation of intellect, preparation for real life, individual benefits, social benefits and physical growth. This study employs qualitative method and is conceptual research that focuses on developing a theory to explain the development of holistic personality, its theoretical framework and methodologies. The research process integrates three domains namely conceptual, methodological and substantive. The findings from this conceptual research will give some benefits to any schools and higher institutions which are practicing integrated curriculum and concern on the development of good personalities for their graduates. This paper present a conceptual framework which explain the characteristics and indicators of holistic personality as reference for educators, academics, counselors, parents for developing personality of a person.